2015
DOI: 10.1002/hec.3267
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medical Marijuana Laws on Body Weight

Abstract: This study is the first to examine the effects of medical marijuana laws (MMLs) on body weight, physical wellness, and exercise. Using data from the 1990 to 2012 Behavioral Risk Factor Surveillance System and a difference-in-difference approach, we find that the enforcement of MMLs is associated with a 2% to 6% decline in the probability of obesity. We find some evidence of age-specific heterogeneity in mechanisms. For older individuals, MML-induced increases in physical mobility may be a relatively important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 90 publications
8
113
0
Order By: Relevance
“…29 states and the District of Columbia have implemented an MML. Common health conditions that qualify patients for legal use of marijuana include cachexia, cancer, epilepsy, HIV/AIDS, muscle spasms, multiple sclerosis, and non-specific pain (Bradford & Bradford, 2016;Sabia, Swigert, & Young, 2017). Many of these conditions overlap with conditions that qualify a worker for SSDI and WC benefits, offering premise for our study.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…29 states and the District of Columbia have implemented an MML. Common health conditions that qualify patients for legal use of marijuana include cachexia, cancer, epilepsy, HIV/AIDS, muscle spasms, multiple sclerosis, and non-specific pain (Bradford & Bradford, 2016;Sabia, Swigert, & Young, 2017). Many of these conditions overlap with conditions that qualify a worker for SSDI and WC benefits, offering premise for our study.…”
mentioning
confidence: 99%
“…We leverage law effective dates collected by Sabia and Nguyen (2016) in our study. 14 These laws offer the variation with which we identify treatment effects in our differences-indifferences models (outlined later in the manuscript).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both the BMI data and the AOR data show significantly lower BMI or rates of overweight or obesity in Cannabis users (BMI: paired t-test P < 0.001; OR 95% CI = 0.53 -0.84) (tables 1 and 2). Further evidence comes from the recent observation that legalization of medical Cannabis at the state level is associated with a rapid decrease in statewide obesity rates (Sabia et al, 2017), and that obese rats exposed to Cannabis extract show reduced rates of weight gain (Levendal et al, 2012). Indeed, the inverse relationship between obesity and Cannabis use led Le Foll et al (Le Foll et al, 2013) to propose Cannabis as a possible therapeutic option for weight loss, and evidence accumulated since then has only strengthened the association.…”
Section: Results: Bmi Datamentioning
confidence: 99%
“…Pagotta et al (Pagotto et al, 2006) suggested that the sedative effects of high doses of Cannabis could reduce food consumption, but Rajavashiseth et al (Rajavashisth et al, 2012) observed detectable effects on BMI at usage rates of four times or less per month (25% of non-users were obese, whereas 16% of people who used Cannabis 1 -4 times/month were obese, P < 0.001). Sabia et al (Sabia et al, 2017) suggested that reduced alcohol use by younger users, and increased physical activity of older users upon initiating medical marijuana use, may be responsible for the observed decrease in BMI. These explanations obviously do not account for increased caloric intake in Cannabis users.…”
Section: Previous Explanations Proposed For Lower Bmi In Cannabis Usersmentioning
confidence: 99%